Pemberdayaan Masyarakat Melalui Pengelolaan Sampah dengan Metode “Muse (Mari Ubah Sampah Menjadi Eco-Enzyme)” pada Karang Taruna Kecamatan Medan Johor - Indra Chahaya S.; Ismil Khairi Lubis; Winni R.E. Tumanggor; Fitri Khairani (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Organic waste that accumulates often disturbs the comfort and causes disease. The waste management system at the Medan Johor Market is still not good because there are no adequate trash cans, organic waste and non-organic waste are not separated, waste disposal at the TPA uses an open dumping system and no reprocessing has been carried out. The purpose of this community service activity is to empower the community through increased participation in waste management using the